Faktor-Faktor yang Mempengaruhi Internet Financial Reporting Pemerintah Daerah dan Implikasinya terhadap Akuntabilitas Laporan Keuangan Daerah - Gusti Indira Alhajjriana; Wahyudin Nor; Rano Wijaya (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2017)
This study aims to investigate: the influence of local revenue on internet financial reporting of local government; the influence of local expenditure on internet financial reporting of local government; the influence of the number of legislative members on internet financial reporting of local government; the influence of the population number on internet financial reporting of local government; and the influence of local government’s internet financial reporting on the accountability of local financial statement.The data of this research comprise 96 out of 32 provincial governments in Indonesia during 2012-2014. The analysis techniques used are logistic regression and ordinal logistic regression. The results of this study show that the local expenditure has influence on local government’s internet financial reporting, while local revenue, the number of legislative members, and the population do not have influence on local government’s internet financial reporting. Moreover, local government’s internet financial reporting does not have influence on local financial statements.Penelitian ini bertujuan untuk mengetahui pengaruh pendapatan asli daerah, belanja daerah, jumlah anggota legislatif, dan jumlah penduduk terhadap internet financial reporting pemerintah daerah; dan pengaruh internet financial reporting pemerintah daerah terhadap akuntabilitas laporan keuangan daerah. Data penelitian ini terdiri dari 96 observasi dari 32 pemerintah provinsi di Indonesia selama tahun 2012-2014. Teknik analisis yang digunakan adalah regresi logistik dan regresi logistik ordinal. Hasil penelitian ini menunjukkan bahwa pengeluaran daerah berpengaruh terhadap internet financial reporting pemerintah daerah, sedangkan pendapatan daerah, jumlah anggota legislatif, dan populasi tidak berpengaruh terhadap internet financial reporting pemerintah daerah. Terlebih lagi, internet financial reporting pemerintah daerah tidak berpengaruh terhadap laporan keuangan daerah.